1998
DOI: 10.1038/25387
|View full text |Cite
|
Sign up to set email alerts
|

Genomic amplification of a decoy receptor for Fas ligand in lung and colon cancer

Abstract: Fas ligand (FasL) is produced by activated T cells and natural killer cells and it induces apoptosis (programmed cell death) in target cells through the death receptor Fas/Apol/CD95. One important role of FasL and Fas is to mediate immune-cytotoxic killing of cells that are potentially harmful to the organism, such as virus-infected or tumour cells. Here we report the discovery of a soluble decoy receptor, termed decoy receptor 3 (DcR3), that binds to FasL and inhibits FasL-induced apoptosis. The DcR3 gene was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
576
4
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 695 publications
(596 citation statements)
references
References 24 publications
(3 reference statements)
9
576
4
7
Order By: Relevance
“…Our results on FasL do not support the Fas -FasL tumour counterattack theory in UC. In addition, DcR3, a decoy receptor for FasL, drew attention as a new molecule working to evade activation of the Fas -FasL system (Pitti et al, 1998). In several other malignancies, DcR3 gene amplification and expression were reported (Roth et al, 2001;Mild et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results on FasL do not support the Fas -FasL tumour counterattack theory in UC. In addition, DcR3, a decoy receptor for FasL, drew attention as a new molecule working to evade activation of the Fas -FasL system (Pitti et al, 1998). In several other malignancies, DcR3 gene amplification and expression were reported (Roth et al, 2001;Mild et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Realtime PCR detection was performed in triplicate on the ABI Prism 7700 using a TaqMan instrument (Applied Biosystems, Tokyo, Japan) as previously described . DcR3 nucleotide sequences for primers are described previously (Pitti et al, 1998). To enable the standardisation of DNA quantity, TaqMan b-actin real-time PCR was performed for each sample, and the results were used to adjust the final results of real-time PCR for DcR3.…”
Section: Real-time Quantitive Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…8 TNFRSF6B could act as decoy receptor to neutralize the proapoptotic effects of Fas ligand, LIGHT, and tumor necrosis factorlike molecule 1A by blocking the interaction with their respective receptors and evading immune surveillance. [8][9][10] Overexpression of TNFRSF6B, originally found in lung and colon cancers and virus-associated lymphoma, is capable of protecting cancer cells against apoptosis. 11 Mounting evidences have shown that TNFRSF6B overexpression is a novel tissue biomarker for predicting tumor invasion and worsening of various chronic inflammatory diseases.…”
mentioning
confidence: 99%
“…11,12 One of the strategies that tumor cells have developed to escape NKG2D-mediated cytolysis by NK cells or cells expressing NKG2D is down-regulating NKG2D ligands such as MICA, 13,14 a process also called shedding. Tumor cells also escape Fas-mediated apoptosis by decreasing surface expression of Fas, 15,16 secreting an antagonistic 'decoy' receptor, 17 expressing anti-apoptotic molecules such as BCL2 family members, 17,18 down-regulating and mutating pro-apoptotic genes such as BAX, APAF1 or Fas. [19][20][21][22][23] In our earlier study 24 we combined the function of NKG2D-mediated cytolysis and Fas-mediated apoptosis into one functional fusion protein by using the extracellular domain of MULT1 and the transmembrane and intracellular domains of Fas in a mouse model.…”
Section: Introductionmentioning
confidence: 99%